1999
DOI: 10.1046/j.1475-1313.1999.00445.x
|View full text |Cite
|
Sign up to set email alerts
|

The development of myopia in Hong Kong children between the ages of 7 and 12 years: a five‐year longitudinal study

Abstract: The purpose of this work was to characterize the development of refractive error in Hong Kong children between the ages of 7 and 12 years. A non self-selected sample of 7-year old children was recruited and followed for 5 years, non-cycloplegic refractions being carried out annually. A life-table was used to determine myopia incidence and prevalence. The mean annual change in the spherical equivalent refraction (SER) was -0.32 D; 75 out of 83 subjects followed for 5 years became less hyperopic or more myopic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 13 publications
2
63
0
Order By: Relevance
“…The prevalence of myopia and the average progression is in good accordance with previous HK studies (Lam et al 1999;Edwards 1999). The Hong Kong children develop myopia earlier than in most other parts of the world.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The prevalence of myopia and the average progression is in good accordance with previous HK studies (Lam et al 1999;Edwards 1999). The Hong Kong children develop myopia earlier than in most other parts of the world.…”
Section: Discussionsupporting
confidence: 89%
“…T he high prevalence, early onset and fast progression of myopia among Hong Kong children is well documented (Lam & Goh 1991;Lam et al 1999;Edwards 1999). The role of nearwork in the etiology of myopia has been reviewed in a recent publication (Rosenfield & Gilmartin 1998), but nearwork as a predominant etiological factor cannot alone explain the present pattern of myopia distribution.…”
mentioning
confidence: 99%
“…The less myopic eye of anisometropic patients seems to behave the same way as in a normal myopic population, tending to shift towards increasing myopia during the first 30 years of life (p < 0.001). 7,14,15 As reported by other authors, the eye with a high degree of myopia tends to have a stable refraction (p = 0.804), unless there is a family history of progressive myopia. 16,17 Similarly, in a strabismic population, Lepard 13 observed that the fixating eye tended to become more myopic, while no appreciable refractive changes were noted in the amblyopic eye.…”
Section: Discussionsupporting
confidence: 62%
“…Although worldwide geographic and ethnic differences in the prevalence of childhood refractive error are well recognized [31][32][33][34][35][36][37], meaningful comparisons between reports in the literature are problematic. The difficulty arises because of different or inadequately described survey and examination methods (such as whether cycloplegia was used), unclear or no uniform definitions for hyperopia and myopia, and differences underlying the age and gender mix of the populations studied.…”
Section: Discussionmentioning
confidence: 99%